A role for protein kinase C activity in interleukin-1 (IL-1) induction of IL-2 gene expression but not in IL-1 signal transduction. - Macchia, G (1990)
Interleukin-1 (IL-1) is known to synergize with phorbol esters in the induction of interleukin-2 (IL-2) expression in T-lymphoid leukemia cells and proliferation of mouse thymocytes. We used a plasmid construct containing the bacterial gene for chloramphenicol acetyltransferase under the control of the human IL-2 promoter to study the nature of this synergism in the murine thymoma cell line EL4. Although IL-1 induction of the IL-2 promoter in these cells required costimulus with phorbol myristate acetate, the signal induced by IL-1 was qualitatively different. We provide evidence to support the hypothesis that the phorbol ester signal is mediated by protein kinase C, and we show that the IL-1 signal is not. That IL-1 and phorbol myristate acetate represent different stimuli was shown by their response to protein kinase C inhibitors, capacity to synergize with increased intracellular free calcium, and requirement for protein synthesis. In addition we show that pretreatment with IL-1 can prime EL4 cells to subsequent activation by concentrations of phorbol esters not normally sufficient to induce IL-2 expression. Pretreated cells remained primed for at least 40 h after removal of the IL-1. Neither phorbol myristate acetate nor a calcium ionophore was capable of preactivating EL4 cells.